Renal lithiasis and inflammatory bowel diseases, an update on pediatric population - Bianchi, Laura; Gaiani, Federica; Bizzarri, Barbara; Minelli, Roberta; Cortegoso Valdivia, Paolo; Leandro, Gioacchino; Di Mario, Francesco; de' Angelis, Gian Luigi; Ruberto, Claudio (Acta Biomedica Atenei Parmensis, 2018)
Background and aim of the work: Historical studies have demonstrated that the prevalence of symptomatic nephrolithiasis is higher in patients with inflammatory bowel disease (IBD), compared to general population. The aim of the review was to analyze literature data in order to identify the main risk conditions described in literature and the proposed treatment. Methods: A research on the databases PubMed, Medline, Embase and Google Scholar was performed by using the keywords “renal calculi/lithiasis/stones” and “inflammatory bowel diseases”. A research on textbooks of reference for Pediatric Nephrology was also performed, with focus on secondary forms of nephrolithiasis. Results: Historical studies have demonstrated that the prevalence of symptomatic nephrolithiasis is higher in patients with inflammatory bowel disease (IBD), compared to general population, typically in patients who underwent extensive small bowel resection or in those with persistent severe small bowel inflammation. In IBD, kidney stones may arise from chronic inflammation, changes in intestinal absorption due to inflammation, surgery or intestinal malabsorption. Kidney stones are more closely associated with Crohn’s Disease (CD) than Ulcerative Colitis (UC) in adult patients for multiple reasons: mainly for malabsorption, but in UC intestinal resection may be an additional risk. Nephrolithiasis is often under-diagnosed and might be a rare but noticeable extra-intestinal presentation of pediatric IBD. Secondary enteric hyperoxaluria the main risk factor of UL in IBD, this has been mainly studied in CD, whether in UC has not been completely explained. In the long course of CD recurrent urolithiasis and calcium-oxalate deposition may cause severe chronic interstitial nephritis and, as a consequence, chronic kidney disease. ESRD and systemic oxalosis often develop early, especially in those patients with multiple bowel resections. Even if we consider that many additional factors are present in IBD as hypomagnesuria, acidosis, hypocitraturia, and others, the secondary hyperoxaluria seems to finally have a central role. Some medications as parenteral vitamin D, long-term and high dose steroid treatment, sulfasalazine are reported as additional risk factors. Hydration status may also play an important role in this process. Intestinal surgery is a widely described independent risk factor. Patients with ileostomy post bowel resection may have relative dehydration from liquid stool, which, added to the acidic pH from bicarbonate loss, is responsible for this process. In this acidic pH, the urinary citrate level excretion reduces. The stones most commonly seen in these patients contain uric acid or are mixed. In addition, the risk of calcium containing stones also increases with ileostomy. The treatment of UL in IBD involves correction of the basic gastrointestinal tract inflammation, restricted dietary oxalate intake, and, at times, increased calcium intake. Citrate therapy that increases both urine pH and urinary citrate could also provide an additional therapeutic benefit. Finally, patients with IBD in a pediatric study had less urologic intervention for their calculosis compared with pediatric patients without IBD.